Pembinaan Penguatan Kapasitas Pengawas Tempat Pemungutan Suara (PTPS) dalam Persiapan Pilkada Tahun 2024 di Kecamatan Masamba Kabupaten Luwu Utara - Septiani, Elya (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
The fact that TPS (PTPS) supervisors often face is ignorance of the form of supervision in elections, especially Regional Head Elections, this is a special concern so it is necessary to increase PTPS capacity strengthening through outreach and training activities. This research aims to analyze the development of strengthening the capacity of polling station supervisors (PTPS) in preparation for the 2024 regional head elections in North Luwu Regency. The research method uses qualitative methods with a participatory approach. Data collection through observation, interviews and documentation. The technique for collecting informants uses a purposive sampling method, namely; TPS Supervisors, Subdistrict and Village Panwaslu, Subdistrict Panwaslu and North Luwu Bawaslu. Training to strengthen the capacity of TPS supervisors is carried out in three stages. Training to strengthen PTPS capacity in the first stage, namely 5-6 October 2024, carried out socialization of understanding of material regarding the principles of election organizers, duties, authority and obligations of TPS supervisors. in the second stage of training to strengthen PTPS capacity which will be carried out on 19-20 October 2024 with the agenda of providing technical implementation of supervision of voting preparations. The third stage of training to strengthen PTPS capacity was carried out on 25-27 October 2024 with the agenda of strengthening PTPS supervisory capacity during the quiet period. The results of the research show that the process of strengthening the capacity of TPS supervisors has been carried out well in accordance with applicable regulations, guided by statutory provisions.